Implementasi Pembelajaran Pendidikan Agama Islam melalui Media Sosial Youtube di Kelas IV SDI Alexandria Kota Tangerang - Diah Nur Asrifah; Yayah Huliatunnisa; Desri Arwen; Ina Magdalena (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
The use of YouTube Social Media is a new thing in learning Islamic Religious Education at SDI Alexandria Tangerang City. The implementation of YouTube Social Media on the material Aku anak Saleh is expected to be able to make students reflect the attitude of Saleh in their daily activities. This study aims to determine how the implementation of Islamic Religious Education Learning through YouTube Social Media in Class IV SDI Alexandria. This research uses descriptive qualitative methods using data collection techniques in the form of interviews, observations and documentation studies. Data validity checks using triangulation. Data were analyzed through the steps of data collection, data reduction, data presentation and conclusion drawing. Interviews were conducted with an Islamic Religious Education teacher and 5 class IV students. The results of this research are that the implementation of Islamic Religious Education Learning via YouTube Social Media in class IV SDI Alexandria is said to be effective and improves students' ability to understand the material of I'm Saleh's Child in accordance with the research focus.